Blue Economy sebagai Instrumen Strategi Maritim China dalam Pengembangan Jalur Sutra - Farhan Firdausi (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
The oceans hold substantial potential for supporting global economic development. China has sought to revitalize the Maritime Silk Road as part of its maritime connectivity agenda under the Belt and Road Initiative (BRI). This qualitative study examines how China integrates blue economy principles into its maritime strategy within the Belt and Road Initiative’s maritime framework. Using thematic analysis of secondary sources, including academic literature, policy reports, and media materials, the study analyzes the role of the blue economy in shaping China’s maritime trade and international cooperation. The findings indicate that the incorporation of blue economy principles functions as an instrument of maritime strategy by facilitating sustainable port development, strengthening maritime logistics networks, and expanding economic partnerships along the Maritime Silk Road. This mechanism enables China to align environmental sustainability with strategic economic objectives while reinforcing its maritime influence within the BRI framework. The study demonstrates how the integration of blue economy principles supports China’s broader maritime strategy and economic diplomacy within the global maritime order.